An NTCP Analysis of Urethral Complications from Low Doserate Mono- and Bi-Radionuclide Brachytherapy. (6th July 2011) - Nuttens, V. E.; Nahum, A. E.; Lucas, S.
Abstract : Urethral NTCP has been determined for three prostates implanted with seeds based on 125 I (145 Gy), 103 Pd (125 Gy), 131 Cs (115 Gy), 103 Pd- 125 I (145 Gy), or 103 Pd- 131 Cs (115 Gy or 130 Gy). First, D U 20, meaning that 20% of the urhral volume receive a dose of at leastD U 20, is converted into an I-125 LDR equivalentD U 20 in order to use the urethral NTCP model. Second, the propagation of uncertainties through the steps in the NTCP calculation was assessed in order to identify the parameters responsible for large data uncertainties. Two sets of radiobiological parameters were studied. The NTCP results all fall in the 19%–23% range and are associated with large uncertainties, making the comparison difficult. Depending on the dataset chosen, the ranking of NTCP values among the six seed implants studied changes. Moreover, the large uncertainties on the fitting parameters of the urethral NTCP model result in large uncertainty on the NTCP value. In conclusion, the use of NTCP model for permanent brachytherapy is feasible but it is essential that the uncertainties on the parameters in the model be reduced.